Exploring the Role of BIM in Knowledge Management in Construction Projects - Rodrigues, Igor Alencar; Azevedo, Vinícius Francis Braga de; Silva Neto, Vicente Estevam da; Kohlman Rabbani, Emilia Rahnemay; Vasconcelos, Bianca M. (National Journal of City Management, 2024)
The non-serialized nature of the construction industry, the dynamic environment of construction sites, and the high turnover of workers are conditions that hinder the application of knowledge management (KM) in the sector. Given this, several studies highlight the use of BIM as a platform capable of optimizing KM. The main objective of this study was to investigate the potential of BIM for KM in construction. To this end, a systematic literature review was conducted, revealing a variety of practical applications of BIM in KM in areas such as occupational safety, project management, and sustainability in facilities management. However, studies are still in the early stages, with limited activities and risks included in the analyses. Moreover, ontology is widely used to structure knowledge in conjunction with a BIM model, followed by case-based reasoning (CBR). Although BIM can optimize KM, its application needs to be scaled up. Future studies should explore the use of machine learning to accelerate the knowledge modeling process.
Keywords: Design for safety; Project Management; Facilities Management